Al-Qur'an Verses Concerning Educational Materials in the Interpretation of Wahbah al-Zuhaily in the Tafsir Al-Munir - Rita Nurjanah; Hafid; Cecep Anwar; Ahmad Sahira Zandi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Thematic interpretation plays a crucial role in shaping an education system that focuses not only on academic aspects but also on students' character and morals. This method allows for in-depth analysis of educational themes in the Quran, ensuring its teachings are relevant to modern conditions. Thus, thematic interpretation can serve as the basis for developing a comprehensive Islamic education curriculum, integrating Islamic values ​​into every aspect of learning. Islamic religious education teaching materials must align with the national curriculum established by the Ministry of Education and Culture, designed to provide a balanced religious education encompassing spiritual, moral, and intellectual aspects.Teaching must integrate Islamic values, including faith (aqidah), morals, and sharia (Islamic law), so that students can apply these values ​​in their daily lives. It is crucial to use credible and relevant sources in developing teaching materials, including classical texts, Quranic interpretations, hadith, and contemporary literature. Teaching materials must also be adapted to the local context and students' needs to ensure they are relevant to the challenges they face. The selection of teaching materials must be based on the desired competency standards, encompassing students' knowledge, skills, and attitudes. The learning process should involve ongoing evaluation to gauge students' understanding of the material. In the digital age, the use of technology such as educational apps and e-learning platforms can enhance the effectiveness of Islamic religious learning by providing interactive features that facilitate independent learning. With this approach, it is hoped that students will not only understand theory but also internalize values ​​in their daily lives, making education a tool for transforming students into ideal human beings.